Night in the city : a novel - McGarrity, Michael (W.W. Norton & Company, 2025)
"Accused of the murder of his former lover, Korean War veteran Sam Monroe is forced to abandon his job as an assistant district attorney and fight to clear his name. Sam Monroe thought his steamy love affair with Manhattan socialite Laura Nielson was dead and buried, but when she didn't show up after unexpectedly calling him late at night and asking to meet, he decides to investigate. He finds her naked on her penthouse balcony, strangled, his dog tags wrapped around her neck. With a bull's-eye on his back as the prime suspect. Sam begins a search for the killer that reveals Laura's involvement with several men, some with ties to a well-known crime family. As circumstantial evidence mounts against him, the cops close in, especially a heavy-handed rogue patrolman carrying a grudge against Sam and looking for serious payback. Forced to operate in the shadows, he relies on the unofficial help of several coworkers in the DA's office and Debora Jean Ryan, a private investigator who offers to assist but has an agenda that she refuses to disclose. As they probe Laura's past looking for clues, they must also figure out Laura's mysterious trip out west, the death of a young man in New Jersey during her childhood, and who is making attempts on Monroe's life."--